INNOVATIVE-TECHNOLOGICAL PRODUCTION DEVELOPMENT ON THE BASIS INTELLECTUALIZATION OF PROCESSES. FOREIGN EXPERIENCE - L. Zelentsova; A. Khakimov (Вестник университета)
The article discusses the current state of internetization industry and the role of digital technologies in the development of economies of European Union, the Asia-Pacific region and the United State. The experience of world leaders in the field of cyber-physical systems integration in industrial processes is analyzed. Programmers for the industrial development of various countries are analyzed on the example of intellectualization all processes. Real examples show that the use of digital technologies and communications creates the conditions for intensive development of the economy. The structure of the concept «Industry 4.0» as a platform to create «smart factories» is presented.